Aspek Hukum terkait Penerbangan Lintas Batas berdasarkan Konvensi Chicago - Delfiyanti, Delfiyanti (Universitas Ekasakti, 2023)
At the time, air transport world have mounted at full speed and seen from to the number of plane type and form which have been yielded. Pursuant to Section 1 Convention of Chicago year 1944 about Civil Air Navigation that every state have exclusive and full of sovereignty of air room residing in above its region of him. This convention also recognize and give rights to state to do interception related to straightening of sovereignty state above its air room. In practice, some time the foreign aeroplane thrust into other state air region without permit beforehand. Therefore enabled a state to do interception in the form of commemoration to the foreign plane to go out from regional room of its air. At certain level, even can be shot if remain to fight against. One side, this action is confessed as part of straightening of state sovereignty. But on the other side, usage of tight interception abusively can generate the fall of victim. Therefore, usage of rights of interception need clear arrangement and strong control.